PERSEPSI AKUNTAN PUBLIK, AKUNTAN PENDIDIK, MAHASISIWA AKUNTANSI, DAN MAHASISIWA PPaK TERHADAP ETIKA PROFESI AKUNTAN - Jefri Sri Indang Susilowati; Rita Anugerah; Al Azhar Lukman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study examines the perception of Public Accountants, Accounting Educators, Students and Student Accounting PPAk to ethical accounting profession. This study uses a survey of Certified Public Accountants in the city of Pekanbaru, Accounting Educators, Students of Accounting at the University of Riau and Riau Islamic University and University Students PPAk in Riau. The data used is primary data collection method of data using questionnaires. Data analysis methods used in this study using independent sample t-test with SPSS version 17.0.This study examined the perceptions of public accountants, accountants educators, students and student accounting PPAk to the principles of professional ethics accountant represented by eight principles: responsibility of the profession, the public interest, integrity, objectivity, competence and professional prudence, confidentiality, professional behavior and technical standards. Based on the test results show that: first, there is a significant difference in perception between public accountant with accounting educators, where the mean value of public accountants is 106.9200 higher than accountants educators is 98.1538. Secondly, there is a significant difference in perception between public accountant with accounting students to ethical accounting profession, seen from the mean value of the two groups is known that the mean value of Certified Public Accountants is higher than the mean 106.9200 Accounting Students is 90.1615.Third, there is a significant difference in perception between public accountant with PPAk students to ethical accounting profession, the difference Judging from the mean value of the two groups is known that the mean value is 106.9200 Public Accountant higher than the mean accountant educators is 97.0000. Fourth, there are significant differences in perceptions between educators and students accountancy accountant Judging from the mean value of the two groups is known that the mean value accountant 98.1538 educators are higher than the mean accounting student is 90.1516. Fifth, there are no significant differences in perceptions between educators and students PPAk accountants against ethics accounting profession, but judging from the mean value of the two groups is known that the mean nilia accountant 98.1538 educators are higher than the mean of students PPAk is 97.0000. Sixth, there are no significant differences in perception between accounting students with student PPAk to ethics accounting profession, but judging from the mean value of the two groups is known that the mean value accounting educators that is higher than the mean 98.1538 accounting student is 90.1516.Keywords: Perception, code of professional conduct accountants, public accountants, accountants, accounting student, student PPAk.